The Effectiveness of Omnichannel Marketing on Customer Loyalty Amid Business Digital Transformation - Rr Dyah Eko Setyowati (Mandalika Journal of Business and Management Studies, 2026)
This study examines the effectiveness of omnichannel marketing on customer loyalty amid business digital transformation. The main problem addressed is the inconsistency of customer experience across multiple channels that affects loyalty in digital business environments. The objective of this research is to analyze how omnichannel marketing influences customer loyalty through integrated and consistent customer experiences. This study uses a qualitative literature review method by analyzing relevant books, journals, articles, and previous research related to omnichannel marketing, customer loyalty, and digital transformation. The data used are secondary data obtained from academic literature sources. The results show that omnichannel marketing significantly enhances customer loyalty by improving consistency, personalization, trust, and customer engagement across channels. In conclusion, omnichannel marketing is an effective strategy in strengthening customer loyalty in the era of digital transformation by creating seamless and integrated customer experiences.